Towards an algorithmic guide to Spiral Galaxies - Fertin, Guillaume; Jamshidi, Shahrad; Komusiewicz, Christian (Theoretical computer science, 2015)
We study the one-player game Spiral Galaxies from an algorithmic viewpoint. Spiral Galaxies has been shown to be NP-hard [6] more than a decade ago, but so far it seems that no one has dared exploring its algorithmic universe. We take this trip and visit some of its corners.